CO2 capture with potassium carbonate solutions: A state-of-the-art review - Borhani, T.N.G. (Elsevier Ltd, 2015)
The potassium carbonate (PC) solution is an important chemical solvent to reduce CO2 emissions due to its advantages of low cost, little toxicity, ease of regeneration, slow corrosiveness, low degradation, and its high stability as well as CO2 absorption capacity. As a result, the PC process has been applied in more than 700 plants worldwide for CO2 and hydrogen sulphide removal from streams like ammonia synthesis gas, crude hydrogen, natural gas, and town gas. This paper provides a state-of-the-art review on the research works on CO2 capture using the PC solution. The studies related to the PC solution comprise three main areas: process, thermodynamics, and kinetics. Important experimental studies as well as modeling and simulation studies are reviewed. Future research directions on CO2 absorption by aqueous PC solution are highlighted and discussed. Â© 2015 Elsevier Ltd.